2013
DOI: 10.1139/cjpp-2012-0359
|View full text |Cite
|
Sign up to set email alerts
|

The effect of female sexual hormones on the intestinal and serum cytokine response after traumatic brain injury: different roles for estrogen receptor subtypes

Abstract: The purpose of this study was to evaluate the effect of female sexual hormones on intestinal and serum cytokines following traumatic brain injury (TBI). Adult female rats were ovariectomized and distributed among the following 9 groups: (i) sham trauma, (ii) TBI (Marmarou's method), (iii) vehicle (dimethylsulfoxide) treated, (iv) estrogen (E2) treated, (v) progesterone (P) treated, (vi) treated with E2+P, (vii) propylpyrazole triol (PPT) treated, (viii) diarylpropionitrile (DPN) treated, and (ix) control. PPT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…The response to neuroinflammation is regulated by estrogen levels via estrogen receptors [44]. Estrogen has been shown to have inhibitory effects on proinflammatory cytokines after diffuse TBI in rats [45]. Although the preinjury estrous stage has no correlation with outcome after experimental TBI in rats [46], female rats have better short-term behavioral outcomes after injury than males, suggesting that exposure to endogenous circulating sex steroids confers some neuroprotection against TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The response to neuroinflammation is regulated by estrogen levels via estrogen receptors [44]. Estrogen has been shown to have inhibitory effects on proinflammatory cytokines after diffuse TBI in rats [45]. Although the preinjury estrous stage has no correlation with outcome after experimental TBI in rats [46], female rats have better short-term behavioral outcomes after injury than males, suggesting that exposure to endogenous circulating sex steroids confers some neuroprotection against TBI.…”
Section: Discussionmentioning
confidence: 99%
“…E 2 -SO 4 has both genomic and non-genomic protective effects following tissue injury, which include stabilizing the blood-brain barrier and neuron excitotoxicity, increasing cell-survival mediators, and modulating inflammatory process via decreasing proinflammatory and increasing anti-inflammatory molecules. [36][37][38][39] Treatment with estrogen following adverse additional circulatory conditions such as soft-tissue trauma and hemorrhage as well as organ ischemia and reperfusion has also been shown to have salutary effects. [40][41][42][43][44] Furthermore, it has been recently verified that early treatment with a single dose of E 2 -SO 4 increased brain cell survival, while decreasing neuronal degeneration, apoptosis, and reactive astrogliosis in a TBI animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting this hypothesis is the finding that the protective female advantage on outcome measures, such as a reduction of BBB permeability and cerebral edema, was attenuated or even completely absent in Ovx-induced surgically hormone-deplete rats (Bramlett and Dietrich, 2001; Suzuki et al, 2004). Exogenous administration of 17βE2 either in the weeks preceding insult or within minutes to hours after injury appears to ameliorate the detrimental impacts of hormone deficiency (Khaksari et al, 2011; O'Connor et al, 2005; Roof and Hall, 2000), the effects of which have been shown to be mediated through a variety of mechanisms including GPER1 and the classical genomic ERα and ERβ pathways as shown via the use of SERMs (Asl et al, 2013; Day et al, 2013; Khaksari et al, 2013). Despite these promising findings, not all studies report a beneficial effect of estrogen treatment among female animals (Bruce-Keller et al, 2007; Lebesgue et al, 2006).…”
Section: Estrogen Neuroprotection In Brain Injurymentioning
confidence: 99%